2015
DOI: 10.1159/000439352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Brain-Derived Neurotrophic Factor G196A and Attempted Suicide: A Case-Control Study in Rural China

Abstract: Background: Suicide is an important public problem, the mechanism of which has not been clarified. Many studies have focused on the molecular, biological and genetic mechanisms of suicide. Brain-derived neurotrophic factor (BDNF) G196A is one of the most leading loci in recent studies, but the results are inconsistent. Methods: We conducted a 1:1 age- and sex-matched case-control study in rural areas of Shandong Province, China. A total of 365 pairs of cases and controls were finally recruited into our study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…23 There was no report of the relationship between the lethality of suicide and the rs6265 SNP in Asian or Korean populations prior to this study. Several studies in Asian populations have reported a higher risk of suicide attempt in subjects with the Met allele or a Met/Met genotype, 13,[15][16][17] although others have reported a significant association between the Val/Val genotype and risk of suicide 27,28 or no association. 11,14,21 Recently, Gonzalez-Castro et al 9 reported increased suicidal risk in the Val/Val genotype group in Asian populations by metaanalysis using data from six previous studies, and this result is partially in line with our research.…”
Section: Discussionmentioning
confidence: 99%
“…23 There was no report of the relationship between the lethality of suicide and the rs6265 SNP in Asian or Korean populations prior to this study. Several studies in Asian populations have reported a higher risk of suicide attempt in subjects with the Met allele or a Met/Met genotype, 13,[15][16][17] although others have reported a significant association between the Val/Val genotype and risk of suicide 27,28 or no association. 11,14,21 Recently, Gonzalez-Castro et al 9 reported increased suicidal risk in the Val/Val genotype group in Asian populations by metaanalysis using data from six previous studies, and this result is partially in line with our research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Val66 (G196) allele and corresponding Val/Val genotype were significantly more frequent in SZ patients with lifetime suicide attempts than in patients without lifetime suicide attempts (58.9% and 51.1% vs. 32.5% and 23.9%, respectively, for allele and genotype comparisons), which was opposite to our expectation. However, two previous studies involving bipolar disorder (Vincze et al, 2008) and major depressive disorder patients with suicide attempts (Perroud et al, 2009) also showed a significant increase in the Val allele compared to those patients without suicide attempts; however, some other studies reported the Met allele and the Met allele–carrying genotypes to be associated with a history of suicide attempts (Iga et al, 2007; Kim & Kim, 2008; Sarchiapone et al, 2008; Spalletta et al, 2010), including a recent meta-analysis (Zai et al, 2012), or no association (Huang & Lee, 2007; Hwang et al, 2006; Pregelj et al, 2011; Ropret et al, 2015; Wang et al, 2015; Zarrilli et al, 2009) in patients with various psychiatric disorders. A possible reason for the inconsistencies in genetic association studies is related to ethnic background.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several genetic studies reported that the BDNF functional Val66Met gene polymorphism (rs6265) may be associated with suicide (Mirkovic et al, 2016;Pregelj et al, 2011;Spalletta et al, 2010;Zarrilli et al, 2009). However, recent studies did not find any relationship of this polymorphism with suicide (Ropret, Zupanc, Komel, & Videtic ˇPaska, 2015;Wang, Wang, Wang, & Jia, 2015). A most recent meta-analysis of 12 studies indicated that the BDNF Met allele is considered the risk allele for suicidal behaviors in subjects with various psychiatric disorders (Zai et al, 2012).…”
mentioning
confidence: 99%
“…In terms of PTSD, Met allele carriers exhibit increased activity in neural structures and appear to be more susceptible to disease development (Lonsdorf et al., 2015). To date, the rs6265 G > A polymorphism has been shown to be associated with many central nervous system diseases, such as Alzheimer's disease, Parkinson's disease, depression, and suicide (Aldoghachi et al., 2019; Brown et al., 2020; Wang et al., 2015). In 2006, Zhang et al conducted the first case–control study on the association between the BDNF rs6265 G > A polymorphism and PTSD susceptibility and found no significant association in a US population (Zhang et al., 2006).…”
Section: Introductionmentioning
confidence: 99%